Studies on Nham-Pla’s Processing by Using Rock Salt and Solar Salt - Mathana Sangjindavong; Pranisa Chuapoehuk; Daungdoen Vareevanich (Agriculture and Natural Resources, 2005)
Nham-Pla (fermented fish cakes) were made from striped snake-head fish (Channa striata), Nile tilapia (Oreochromis niloticus), striped catfish (Pangasius hypophthalmus), and hybrid catfish (Clarias macrocephalus x Clarias gariepinus). The results of the organoleptic test of uncooked Nham-Pla prepared from rock salt showed differences (p<0.05) in appearance, texture, odor and average acceptability scores with the exception for dark meat flesh from hybrid catfish which received the lowest acceptability score of color. The organoleptic tests of cooked Nham-Pla prepared by using rock salt revealed that Nham-Pla made from striped catfish received the highest acceptability score for the appearance characteristic and there were no differences in odor, taste and average acceptability score for both samples prepared from rock salt and solar salt. Nham-Pla made from Nile tilapia with solar salt received the lowest acceptability score, but they received the highest acceptability score for texture. Nham-Pla made from snake-head fish using solar salt received better acceptability scores than Nham-Pla prepared by using rock salt. According to the results, rock salt and solar salt were important for Nham-Pla preparation based on species of fresh water fish and some of their characteristics.